Reflections on the Entrepreneurship Ecosystem in Albania - Mersini, Arjola; Qosja, Ermira (Research Papers, 2025)
Entrepreneurship and innovation are essential to any country’s economic development. Albania has taken important steps over the last ten years to create a supportive ecosystem for entrepreneurship, with a special focus on young people and technology. Public and private institutions have contributed to the creation of innovation centers, enterprises, and start-up financing programs.This paper will present the current situation of small businesses in Albania influenced by public policies undertaken in the last 10 years. By studying the development of the entrepreneurship ecosystem during the last ten years, this study aims to identify the successes and challenges of the policies followed, as well as to give recommendations for their improvement in order to help the economic development of the country through these changes.